2016
DOI: 10.1134/s1995078016020051
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric particles of tobacco mosaic virus as a platform for the development of next-generation nanovaccines

Abstract: The production of vaccines and other proteins in plants for medical purposes offers a number of advantages over other expression systems. The tobacco mosaic virus (TMV) is an appropriate model for the development of a variety of vectors, including those used for the assembly of chimeric particles carrying heterologous peptides on the surface and inducing an effective immune response. To overcome the problems arising during the assembly of such particles from recombinant subunits of the coat protein, peptide li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The N and C termini of the TMV capsid point outwards from an assembled TMV disk ( Fig. 1A) and majority of previous vaccine design efforts have used these N and C termini to display epitopes (41,(49)(50)(51)(52). Dedeo et al (53) reported a "circular permutant" of TMV where the N and C termini were re-engineered to the inner pore and a short loop was placed to close the sequence gap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N and C termini of the TMV capsid point outwards from an assembled TMV disk ( Fig. 1A) and majority of previous vaccine design efforts have used these N and C termini to display epitopes (41,(49)(50)(51)(52). Dedeo et al (53) reported a "circular permutant" of TMV where the N and C termini were re-engineered to the inner pore and a short loop was placed to close the sequence gap.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized an open source particle technology based on the tobacco mosaic virus (TMV) VLP for this design effort. TMV under physiological conditions assembles into an 18-nm disk that can also further assemble into rod shaped VLPs of up to 300 nm in size (41). The TMV size range and, its repetitive, symmetric, and high-density display of epitopes make them highly attractive for antigen presentation and induction of high titer antibodies (42).…”
mentioning
confidence: 99%
“…We chose TMV, a 300 nm × 18 nm tubular RNA plant virus, as a model vaccine biomacromolecule owing to extensive data on its in vivo performance as a carrier for engineered and chemically conjugated epitopes in vaccine development (Scheme ). This chemical modifiability, which can occur on both interior and exterior surfaces independently, has given TMV a unique appeal beyond vaccine development as the structure tolerates attachment of dyes, sensors, , contrast agents, and bioactive molecules. , The multivalent nature of TMV comes from its 2130 identical coat proteins arranged helically around a 4 nm central pore where the viral RNA is located.…”
mentioning
confidence: 99%
“…This chemical modifiability, which can occur on both interior and exterior surfaces independently, has given TMV a unique appeal beyond vaccine development as the structure tolerates attachment of dyes, sensors, , contrast agents, and bioactive molecules. , The multivalent nature of TMV comes from its 2130 identical coat proteins arranged helically around a 4 nm central pore where the viral RNA is located. This allows many bioconjugations to the same virus particle, increasing local concentration of active sites and immobilizing them, which is one reason it is thought to be such a useful platform for vaccine development. …”
mentioning
confidence: 99%
“…The production of chimeric viral particles with efficient virion assembly has been the objective of several studies. To achieve this, certain methods have been based to limit the steric hindrance of the modified coat protein by incorporation of the linker peptides between the viral coat protein and the fused peptide [81]. Furthermore, applying proteolytic site region, suppressed stop codon, -ribosomal skip‖ of translation sequences (such as 2A peptide of the foot-and-mouth disease virus) between the heterologous peptide and the coat protein have been used where the fused product is synthesized along with the wild type coat protein [82].…”
Section: -Limitations Of Current Vlp Production Platformsmentioning
confidence: 99%